Analisis Framing Pemberitaan Maraknya Mural Kritikan Terhadap Pemerintah Pada Masa Pandemi di Media Tempo.co dan Media Indonesia (Periode 12 Agustus 2021 - 01 September 2021) (Universitas Negeri Surabaya, 2022)
The incident of the rise of murals criticizing the government during the pandemic carried out by the public to express unrest due to the COVID-19 pandemic crisis was responded to by the authorities by removing murals and summoning mural makers for various reasons. According to many parties, the reaction of the apparatus in removing murals is considered a form of backwardness to democracy and the principle of freedom of expression in Indonesia. The media as one of the pillars of democracy plays a role in supervising power, so it is important to see its role in the reporting process of the rampant mural action which was marked by the removal of murals by the authorities. However, there are many interests that affect the reporting of a media, one of which is the interest of media ownership. Therefore, the media Tempo.co and Media Indonesia were chosen as research subjects to compare the framing of the news in the incident of the rise of murals criticizing the government during the pandemic. To see the reality behind the discourse of the mass media, framing analysis is used with the model proposed by Zhongdang Pan and Gerald M. Kosicki. The results found that both media framed the event with the interests of each media. Tempo.co framed the event by taking sides with the mural action by the community. Meanwhile, Media Indonesia tends to frame events by glorifying the removal of murals. Keywords: Framing, Media, Mural, Tempo.co, Media Indonesia